PERFORMANCE PROJECTS OF ARTS STUDENTS AS A FACTOR IN SHAPING NATIONAL CONSCIOUSNESS - KONDRATENKO, Ganna; KYRYLENKO, Yana; IVANENKO, Olena; SYNIEOK, Vira; KALIIEVSKYI, Kostiantyn; TKACHENKO, Inna (Studia Universitatis Babes-Bolyai Musica, 2026)
The study of the mechanisms underlying the development of national consciousness is of great importance for cultural promotion, as it fosters personal identification with the nation and its traditions. This study aimed to assess the benefits of artistic and choreographic projects for the development of national consciousness among students pursuing higher education in the arts. The study utilised correlation analysis, the Student’s t-test, a Likert scale, and expert assessment of students’ perceptions of vocal and choreographic projects. The authors identified factors that influence the formation of national consciousness in vocal projects (repertoire, intonation, arrangement, symbolic elements, interpretation). In choreographic projects, these factors include movement, rhythm, imagery, symbolism and synchronisation. It was found that the trends in the perception of elements of national consciousness in vocal projects include the melodic basis of the composition, an emphasis on ornamentation, and the choice of performance interpretation. For the choreographic projects, these indicators are the emotionality of the staging, selected movements, and the stage image. The students’ performances of the traditional composition “Oi u luzi chervona kalyna” (4.3 points) and the contemporary piece “Shum” (4.2 points) demonstrated the advantages of the folk compositions in conveying elements of national consciousness. In choreographic projects, the highest level was demonstrated in the creation of the modern jazz dance improvisation with ethnic elements “Rodynnyi oberih” (4.5 points), due to the high level of choreographic plasticity. Understanding the criteria for expressing national consciousness in artistic projects contributes to the popularisation of art and intercultural development.